2021
DOI: 10.1093/ehjopen/oeab024
|View full text |Cite
|
Sign up to set email alerts
|

One-year impact of bariatric surgery on left ventricular mechanics: results from the prospective FatWest study

Abstract: Aims Patients with severe obesity are predisposed to left ventricular (LV) hypertrophy, increased myocardial oxygen demand, and impaired myocardial mechanics. Bariatric surgery leads to rapid weight loss and improves cardiovascular risk profile. The present prospective study assesses whether LV wall mechanics improve 1 year after bariatric surgery. Methods and results Ninety-four severely obese patients [43 ± 10 years, 71% wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Our meta-analysis documented that the LVEF did not change significantly after bariatric surgery. Some studies did not report any LVEF improvement [ 16 , 19 , 20 , 22 , 26 ]; this was not the case with GLS, which was significantly improved in all examined studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The present meta-analysis also demonstrated that only GLS, but not LVEF, was improved regardless of the duration of the follow-up.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our meta-analysis documented that the LVEF did not change significantly after bariatric surgery. Some studies did not report any LVEF improvement [ 16 , 19 , 20 , 22 , 26 ]; this was not the case with GLS, which was significantly improved in all examined studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The present meta-analysis also demonstrated that only GLS, but not LVEF, was improved regardless of the duration of the follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, 102 studies were reviewed; of these, 77 did not report data on myocardial mechanics, and 24 were reviews, commentary, editorial articles, case reports and studies including less than 10 participants. Thus, a total of 13 studies including patients treated with bariatric surgery for a period longer than one month and containing echocardiographic data of interest were included in the final review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] ( Figure 1 ). According to the NOS, the quality of the studies ranged from 6 to 9 (i.e., a score that identifies studies of fair or good quality) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 LV hypertrophy was identified as recommended in populations with higher prevalence of obesity as LV mass indexed for height 2.7 ≥49.2 g/m 2.7 in men and ≥46.7 g/m 2.7 in women. [20][21][22] The ratio of LV end-diastolic posterior wall thickness/internal diameter (the relative wall thickness) indicated concentric LV geometry when ≥0.43. 23 LV systolic function was assessed by both EF and global left ventricular longitudinal strain (GLS; low if less negative than −16.7% in men and <−17.8% in women) using all 3 standard apical views.…”
Section: La Size and Functionmentioning
confidence: 99%